2008
DOI: 10.1111/j.1744-6155.2008.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Kangaroo Care on Behavioral Responses to Pain of an Intramuscular Injection in Neonates

Abstract: KC given before injection seems to effectively decrease pain and should be considered for minor invasive procedures in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 28 publications
0
22
0
2
Order By: Relevance
“…No significant decrease in pain (P,0.57) was associated with parent-led tactile distraction. 30 In contrast, Kashaninia et al 31 found, in results from the neonatal infant pain scale (NIPS), significantly lower pain associated with vaccination (P,0.001) when a mother held her infant skin-to-skin with gentle pressure on the back before and during the injection.…”
Section: Bowen and Dammeyermentioning
confidence: 95%
See 2 more Smart Citations
“…No significant decrease in pain (P,0.57) was associated with parent-led tactile distraction. 30 In contrast, Kashaninia et al 31 found, in results from the neonatal infant pain scale (NIPS), significantly lower pain associated with vaccination (P,0.001) when a mother held her infant skin-to-skin with gentle pressure on the back before and during the injection.…”
Section: Bowen and Dammeyermentioning
confidence: 95%
“…44 Three studies investigated the influence of positioning on vaccination pain (see Table 3). Kashaninia et al 31 investigated a developmentally appropriate positioning known as Kangaroo-Care (KC) on vaccination related pain. KC requires the infant, wearing only a diaper, be placed on the bare skin of a parent.…”
Section: Patient Positioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Sources of repeated pain in the neonatal period are the invasive procedures needed to obtain bilirubin and glucose samples, testing blood for phenylketonuria, and administration of Vitamin K and Hepatitis B injections prior to discharge in healthy full term newborns. SSC has been confirmed as an effective non-pharmacologic pain reduction intervention when provided by the mother or father [13] [14], and when given alone [15] [16] [17] or in combination with breastfeeding [18], sucrose [19], and rocking [20]. SSC relieves pain from heel-stick [21] [22] [23], injection [15] [16] [24], or venipuncture [25].…”
Section: Introductionmentioning
confidence: 99%
“…SSC has been confirmed as an effective non-pharmacologic pain reduction intervention when provided by the mother or father [13] [14], and when given alone [15] [16] [17] or in combination with breastfeeding [18], sucrose [19], and rocking [20]. SSC relieves pain from heel-stick [21] [22] [23], injection [15] [16] [24], or venipuncture [25]. A Cochrane analysis of randomized trials of SSC's pain reduction effects in preterm newborns showed that it is highly effective in reducing the pain associated with painful procedures [26].…”
Section: Introductionmentioning
confidence: 99%